The effect of selected feed mixtures on the duodenal morphology: comparison study - Makovický, Peter; Chrenková, Mária; Makovický, Pavol; Fľak, Pavel; Formelová, Zuzana; Novosadová, Vendula; Rajský, Matúš; Vannucci, Luca (Physiological research, 2018)
The objective of this work was to compare the effect of selected feed mixtures on the duodenal morphology. One-hundred-four rats of the Wistar strain were divided to thirteen groups per eight rats. The experiment started in 35-day-old rats after birth and lasted for 32 days. The groups (A-M) were fed by commercial diet, 85 % wheat and 15 % oat diet, 85 % wheat and 15 % triticale, 85 % wheat and 15 % barley, 85 % wheat and 15 % amaranth, 85 % wheat and 15 % lantern, 85 % wheat and 15 % buckwheat, 100 % wheat, 100 % white lupine, 100 % flock peas - variety Garden, 100 % native peas - variety Garden, 100 % native peas - variety Zekon or 100 % extruded peas - variety Zekon diet, respectively. Samples from the duodenum were taken. The height of the villi and the depth of the crypts were measured. The tallest villi were measured in group F (474.33+/-114.36 microm) and the shortest villi were observed in group B (294.08+/-88.52 microm). The deepest crypts were measured in group K (166.41+/-35.69 microm) and the shallowest crypts were observed in group E (77.85+/-17.61 microm). The work documents that gluten-free and classical cereals combination can be a better choice for people who want to limit the gluten content of the diet.
Keywords: krmivo pro zvířata; Animals; Edible Grain; Animal Feed; Pisum sativum; Rats; Intestinal Mucosa; Duodenum; Diet, Gluten-Free; Rats, Wistar; střevní sliznice; duodenum; zvířata; jedlá semena; krysa rodu Rattus; hrách setý; bezlepková dieta; potkani Wistar